Graphene‐sealed Si/SiN cavities for high‐resolution in situ electron microscopy of nano‐confined solutions (Phys. Status Solidi B 12/2016). Issue 12 (December 2016) - Rasool, Haider; Dunn, Gabriel; Fathalizadeh, Aidin; Zettl, Alex
Abstract : Rasool et al. (pp.2351–2354 ) have developed a method to construct well‐defined liquid containers with graphene windows. These containers are remarkably robust and can remain intact in the harsh imaging environments required for electron microscopy. The authors demonstrate that gold nanoparticles suspended in a phosphate buffer solution, a common biological buffer, can easily be imaged using a TEM. The confined nanoparticles can be imaged on multiple length scales, down to 3D atomic resolution motion. These liquid cell containers have broad applications and may be used to study complex nanoparticle assemblies with more complex motions in a fully hydrated state.